Penerapan Metode Full Costing dalam Menentukan Harga Pokok Produksi pada Bumdes Sukoharjo untuk Meningkatkan Efisiensi - Muhammad Khoirul Fattah; Tri Hesti Utaminingtyas; Gentiga Muhammad Zairin (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to analyze the application of the full costing method in determining the cost of goods sold at a Sukoharjo Village-Owned Enterprise (BUMDes). The full costing method is an approach that assigns all production costs, both fixed and variable, to the product. It is expected to provide more accurate cost information than the traditional method currently used by BUMDes. This study used a qualitative descriptive approach, using a case study of a BUMDes Sukoharjo that produces traditional foods such as clorot, geblek, and lanting. Data collection techniques included interviews, observation, and documentation.The results indicate that the method currently used by BUMDes Sukoharjo does not capture all production costs, particularly equipment depreciation and other fixed overhead. Calculating the cost of goods sold using the full costing method yields a higher value than the previous method. This difference occurs because the full costing method comprehensively considers all cost elements, providing a more accurate basis for setting selling prices. By implementing the full costing method, BUMDes can improve cost management efficiency and obtain more accurate information for managerial decision-making. Furthermore, applying the full costing method enables BUMDes to better understand the impact of fixed costs on the overall profitability of their products. By factoring in all costs, including overheads and depreciation, BUMDes can make more informed decisions regarding pricing strategies and resource allocation. This method also allows for greater transparency in cost structures, which is essential for effective financial planning and budgeting. Ultimately, the full costing method will contribute to improved financial sustainability and long-term profitability for BUMDes Sukoharjo, helping them navigate challenges in the competitive market of traditional food production.